The Good Ones - Weinstein, Bruce (Ascent Audio, 2019)
Employers look for two things when hiring or promoting people: knowledge and skill. They rarely, if ever, consider character. Yet character is the key to extraordinary business success. The Good Ones presents ten crucial qualities of high-character employees, qualities that enhance employee satisfaction, client relationships, and the bottom line. You'll hear stories from managers and employees across the U.S. and beyond who reveal how honesty, courage, loyalty, and patience have helped their organizations maintain an edge over the competition. Each chapter is devoted to a single quality of character and ends with questions employers can use to hire and promote the Good Ones-people who are consistently honest, accountable, fair, and grateful. Whether you're looking to bring new people into your organization or seeking a job or promotion yourself, The Good Ones will help you appreciate in practical terms why character is the missing link to excellence.